Closing the Gap: A Novel Metric of Change in Performance - Katuramu, Richard; Wallenta, Jeanna; Semitala, Fred C.; Amanyire, Gideon; Kampiire, Leatitia; Namusobya, Jennifer; Kamya, Moses R.; Havlir, Diane; Geng, Elvin (East African journal of applied health monitoring and evaluation, 2019)
Interventions to improve performance of global programs in the HIV cascade of care are widespread and increasing the focus of implementation science. At present, however, there is no clear consensus on how to conceptualize their improvement at the program level. The commonly used measures of association, based on ratios of probabilities (or odds), have well-known defects in public health applications. They yield large effect sizes even when the absolute effects, and therefore the public health impact, are small. On the other hand, risk differences create problems because settings with higher baseline values are penalized. We aim to examine ways of quantifying improvement in each health center of a cluster-randomized trial in Uganda to accelerate antiretroviral therapy initiation among HIV-infected adults.
Keywords: Gap; Performance; Novel metric